Hedgehog signaling and the glioma-associated oncogene in cancer radioresistance - Zhang, Li; Zhang, Yuhan; Li, Kaixuan; Xue, Shuai (Frontiers in Cell and Developmental Biology, 2023)
Tumor radioresistance remains a key clinical challenge. The Hedgehog (HH) signaling pathway and glioma-associated oncogene (GLI) are aberrantly activated in several cancers and are thought to contribute to cancer radioresistance by influencing DNA repair, reactive oxygen species production, apoptosis, autophagy, cancer stem cells, the cell cycle, and the tumor microenvironment. GLI is reported to activate the main DNA repair pathways, to interact with cell cycle regulators like Cyclin D and Cyclin E, to inhibit apoptosis via the activation of B-cell lymphoma-2, Forkhead Box M1, and the MYC proto-oncogene, to upregulate cell stemness related genes (Nanog, POU class 5 homeobox 1, SRY-box transcription factor 2, and the BMI1 proto-oncogene), and to promote cancer stem cell transformation. The inactivation of Patched, the receptor of HH, prevents caspase-mediated apoptosis. This causes some cancer cells to survive while others become cancer stem cells, resulting in cancer recurrence. Combination treatment using HH inhibitors (including GLI inhibitors) and conventional therapies may enhance treatment efficacy. However, the clinical use of HH signaling inhibitors is associated with toxic side effects and drug resistance. Nevertheless, selective HH agonists, which may relieve the adverse effects of inhibitors, have been developed in mouse models. Combination therapy with other pathway inhibitors or immunotherapy may effectively overcome resistance to HH inhibitors. A comprehensive cancer radiotherapy with HH or GLI inhibitor is more likely to enhance cancer treatment efficacy while further studies are still needed to overcome its adverse effects and drug resistance.